Estudo epidemiológico das alterações vocais em crianças de 06 a 10 anos em Belo Horizonte - Raquel Buzelin Nunes (2017)
The prevalence of dysphonia during childhood has been studied over the years in an attempt to better understand that speech issue that becomes evident upon evaluation by speech therapists, also taking into account the social relevance of the problem. This research hypothesizes that the number of works on dysphonia is still very restricted, and that the differences between their results are quite significant. Therefore, the objective of the present work was estimate the prevalence of childhood dysphonia, describe its epidemiological profile, evaluate the auditory-perceptual, acoustic and vocal characteristics of dysphonia, and its association with socioeconomic and behavioral variables and with the voice-related quality of life in children aged between six and 10 years old. This was an observatory, transversal study, which evaluated 420 children from public and private schools in Belo Horizonte, Brazil. These children had their voices evaluated using auditory-perceptual and acoustic tests. Besides, the socioeconomic, behavioral and the voice-related quality of life were assessed through a questionnaire answered by parents/guardians. The integrative review of the studies evaluating the prevalence of childhood dysphonia revealed differences among their methodologies, what could explain the discrepancy between results. We observed an important prevalence of dysphonia among children between six and 10 years of age, as well as a positive association between dysphonia and vocal and behavioral characteristics. The present study evidenced the importance of a population-based to assess the prevalence of dysphonia among children, and of using reliable and validated methodologies. In conclusion, according to previous studies, one should always take into account vocal and behavioral characteristics, and the voice-related quality of life in children aged between six and 10 years old. The prevalence found in this work was 23%. Voice quality predominance was roughness and breathing with vocal attack. Gender and behavior was relevant for the presence of dysphonia at this age. The socioeconomic condition did not influence dysphonia prevalence. Studies on the prevalence of dysphonia among children are of great value, since vocal alterations constitute an issue of public health and an early treatment is of extreme importance in order to prevent the condition from becoming more serious along the years and from affecting the emotional development of the patient.